The gender and HIV/AIDS library (UNIFEM New YorkUS, 2005)
Presents a collection of resources including research, publications, training tools, and multi-media advocacy materials from the UNIFEM/UNAIDS Gender and the HIV/AIDS Web Portal.
Keywords: HIV